Kensiu,s native lexical items-natural and language heritage under threats? - Alias Abd Ghani,; Salasiah Che Lah,; Fazrul Azmi Zulkifli, (Environmental Management Society, Malaysia, 2011)
This article reports on the study of the native lexical items of Kensiu people in Lubuk Legong. Baling in relation to their natural heritage, viz, flora and fauna. ite examines the lexical choice of kensiu people of their everyday language use particulayly when referring to words associated with their surrounding natural environment.In light of the rapid modernization process which takes place within the kensiu community right now, there is a tendency for the communiy to shift their word choice to a more dominant language i.e. Malay language. This article also reports on the extent to which the Kensiu maintain their native lexical items in particular for the flora and fauna as part of tehir language heritage and the sociolinguistic phenomenon of language shift from native Kensiu to malay words as a result of the rapid changing of their environment and lifestyles.